2001
DOI: 10.1046/j.1365-2567.2001.01305.x
|View full text |Cite
|
Sign up to set email alerts
|

Failure to induce enhanced protection against tuberculosis by increasing T‐cell‐dependent interferon‐γ generation

Abstract: SUMMARYWe evaluated the use of recombinant human interleukin-6 (rhIL-6) and a monoclonal antibody speci®c for interferon-c (IFN-c) as co-adjuvants in a subunit vaccine against tuberculosis consisting of the culture ®ltrate proteins of Mycobacterium tuberculosis (ST-CF) emulsi®ed in the adjuvant dimethyl-dioctadecylammonium bromide (DDA). Both the addition of rhIL-6 and the neutralization of IFN-c resulted in an increased T helper type 1 (Th1) response characterized by enhanced IFN-c production and cell prolife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
49
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 29 publications
5
49
0
Order By: Relevance
“…Finally, there are also implications in the design of vaccines which are frequently screened based on their ability to induce strong IFN-␥ responses. In this regard, we have shown that IFN-␥ may interfere with the development of protective immune responses to tuberculosis during vaccination with mycobacterial proteins (21).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, there are also implications in the design of vaccines which are frequently screened based on their ability to induce strong IFN-␥ responses. In this regard, we have shown that IFN-␥ may interfere with the development of protective immune responses to tuberculosis during vaccination with mycobacterial proteins (21).…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that increasing the expression of endogenous IFN-␥ does not necessarily lead to enhanced protection from mycobacterial infection (50). Quite to the contrary, IFN-␥ and NOS2 have also been implicated in modulating the local cellular response to mycobacterial infection by down-regulating lymphocyte activation and by driving T cells into apoptosis, which may ultimately lead to a deteriorated protective immune response (41,51,52).…”
Section: Discussionmentioning
confidence: 99%
“…Induction of Th1 responses may not be relevant, since M. tuberculosis rapidly does this anyway. Furthermore, in experimental animals, manipulations that increase the Th1 response still further than is achieved by BCG vaccine alone, do not provide any additional protection [29,30]. Enough Th1 is enough.…”
Section: Implications For Vaccine Designmentioning
confidence: 99%